Suppressed Deep Traps and Bandgap Fluctuations in Cu2CdSnS4 Solar Cells with ≈8% Efficiency. Issue 45 (25th October 2019) - Hadke, Shreyash; Levcenko, Sergiu; Sai Gautam, Gopalakrishnan; Hages, Charles J.; Márquez, José A.; Izquierdo‐Roca, Victor; Carter, Emily A.; Unold, Thomas; Wong, Lydia H.
Abstract: The identification of performance‐limiting factors is a crucial step in the development of solar cell technologies. Cu2 ZnSn(S, Se)4 ‐based solar cells have shown promising power conversion efficiencies in recent years, but their performance remains inferior compared to other thin‐film solar cells. Moreover, the fundamental material characteristics that contribute to this inferior performance are unclear. In this paper, the performance‐limiting role of deep‐trap‐level‐inducing 2CuZn +SnZn defect clusters is revealed by comparing the defect formation energies and optoelectronic characteristics of Cu2 ZnSnS4 and Cu2 CdSnS4 . It is shown that these deleterious defect clusters can be suppressed by substituting Zn with Cd in a Cu‐poor compositional region. The substitution of Zn with Cd also significantly reduces the bandgap fluctuations, despite the similarity in the formation energy of the CuZn +ZnCu and CuCd +CdCu antisites. Detailed investigation of the Cu2 CdSnS4 series with varying Cu/[Cd+Sn] ratios highlights the importance of Cu‐poor composition, presumably via the presence of VCu, in improving the optoelectronic properties of the cation‐substituted absorber. Finally, a 7.96% efficient Cu2 CdSnS4 solar cell is demonstrated, which shows the highest efficiency among fully cation‐substituted absorbers based on Cu2 ZnSnS4 . Abstract : The higher photoluminescence yield and reduced bandgap fluctuations due to the substitution of Zn with Cd in Cu2 ZnSnS4 are attributed to the suppression of deep‐trap‐level‐inducing 2CuZn +SnZn defects. The enhanced nonradiative recombination due to 2CuZn +SnZn is revealed as an important performance‐limiting factor in Cu2 ZnSnS4 solar cells. A 7.96% efficient Cu2 CdSnS4 solar cell with reduced bandgap fluctuations and deep traps is demonstrated.